2021
DOI: 10.3389/fnins.2021.680932
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized COVID-19 Patients Were Five Times More Likely to Suffer From Total Sleep Deprivation Compared to Non-COVID-19 Patients; an Observational Comparative Study

Abstract: Objectives: Sleeping disorders are a common complaint in patients who suffer from an acute COVID-19 infection. Nonetheless, little is known about the severity of sleep disturbances in hospitalized COVID-19 patients, and whether these are caused by disease related symptoms, hospitalization, or the SARS-CoV-2 virus itself. Therefore, the aim of this study was to compare the quality and quantity of sleep in hospitalized patients with and without COVID-19, and to determine the main reasons for sleep disruption.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
1
13
0
2
Order By: Relevance
“…Among patients hospitalized for COVID-19, a recent observational comparative study assessing quality and quantity of sleep, confirmed that hospitalized COVID-19 patients were five times more likely to suffer from total sleep deprivation compared to non-covid patients [ 97 ]. It is still not clear if sleep disturbances can be promoted by the hospitalization in itself [ 98 ] or by an effect of symptoms such as anxiety or dyspnea [ 99 ] or if the penetration of the virus in the CNS (cerebrospinal fluid) may have an influence on them [ 100 ].…”
Section: Sleep Deprivation Immune System and Viral Infectionsmentioning
confidence: 99%
“…Among patients hospitalized for COVID-19, a recent observational comparative study assessing quality and quantity of sleep, confirmed that hospitalized COVID-19 patients were five times more likely to suffer from total sleep deprivation compared to non-covid patients [ 97 ]. It is still not clear if sleep disturbances can be promoted by the hospitalization in itself [ 98 ] or by an effect of symptoms such as anxiety or dyspnea [ 99 ] or if the penetration of the virus in the CNS (cerebrospinal fluid) may have an influence on them [ 100 ].…”
Section: Sleep Deprivation Immune System and Viral Infectionsmentioning
confidence: 99%
“…The authors surveyed COVID-19 patients during their hospital stay and discovered that COVID-19 patients reported a complete lack of sleep five times more often than other hospital patients, but the average total sleep time differed between the groups by only 15 min. However, the authors pointed out a different distribution of sleep time among the two groups, namely, in COVID-19 patients, it was often 0 h of sleep or more than 13 h of sleep, while in the COVID-19 negative group, in most cases, this time oscillated around the average of 6 h [ 138 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, among patients with MDD or BD, sleep deprivation is associated with a subsequent improvement in mood or the development of a (hypomanic) episode [ 128 , 129 , 130 , 131 ]. In relation to COVID-19, sleep disturbances and insomnia are reported by patients and described by the authors of the studies relatively often [ 3 , 137 , 138 ]. This is quite a unique feature of COVID-19 and is strongly associated with the development of mania and should therefore be taken into account in the overall assessment of the risk of developing BD after COVID-19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of improvement was to be expected, because many studies show final wake times in hospitalized patients of even before 6:00 am , with the main cause for these early awakenings being hospital staff. 50 , 51 , 52 …”
Section: Discussionmentioning
confidence: 99%